The closing of forensic psychiatric hospitals in Italy: determinants, current status and future perspectives: a scoping review - Di Lorito, Claudio; Castelletti, Luca; Lega, Ilaria; Gualco, Barbara; Scarpa, Franco; Völlm, Birgit (Elsevier, 2017)
Introduction. Italy is the only country in the world to have closed forensic psychiatric hospitals and converted to fully-residential services. The international interest around this reform has not been matched by research. This scoping review aims to report the determinants of the reform, the most updated information on how the system operates, its benefits and its challenges. We further aim to discuss the implications for policy, research and practice.